The effect of seepage flow on movable solid materials research in debris flow experiments - Yang, Shun; Gao, Meiben; Jiao, Jiaxua; She, Tao; Chen, Kun (Frontiers in Earth Science, 2022)
Debris flows is one of the most common natural disasters in mountainous areas, posing a seriously risk to local people’s life and property. It is fundamental basis to study the criteria for movement of solid materials subjected to seepage flow and surface flow for the purpose of prevent this hazard. Therefore, mechanical analysis methods and laboratory experiments were used to study the effect of seepage flow on movable solid materials in debris flow. First, the definition of movable solid materials was proposed. Then, a geological model of debris flow is established considering saturated seepage flow. Finally, through mechanical analysis, formulas for dynamical force and resistance force are derived. The results show that the dynamical force and resistance force increase linearly with depth when the geologic model is homogenous and the seepage flow saturates the entire debris layer. It also indicated that pore-water pressure is one of the most important factors for causing debris flow, especially when the slope angle exceeds 12°. Through comparing the results of tests and theoretical analysis under saturated seepage flow, the discrepancy is only 1.3% to 24.2%, showing that the formulas are fairly reliable. The motion of the solid materials should be described as a mechanical problem rather than a statistic qualitative description. The research contributes to the source volume calculation of small debris-flow watersheds and advances the study of the movable solid materials in complex dynamic conditions.